FRI0434 Prevalence of Structural Cardiac Disease and Diastolic Dysfunction in Axial Spondyloarthritis: A Prospective Case-Control Study. (15th July 2016) - Reejhsinghani, R.; Brown, K.M.; Schiller, N.B.; Yoon, G.; Foster, E.; Gensler, L.S.
Abstract : Background: Aortic dilation, aortic insufficiency (AI) and diastolic dysfunction (DD) have been described as complications of Ankylosing Spondylitis (AS), although their prevalence remains uncertain. Newer therapies for Axial Spondyloarthritis (AxSpA) may have further influenced the prevalence of cardiac disease. Prior studies were small and uncontrolled, resulting in controversial recommendations for routine echocardiographic screening of AxSpA patients. Objectives: The objective of our study was to describe the prevalence of structural heart disease (SHD) and DD among a cohort of AxSpA patients matched with a healthy control population. Methods: Prospective transthoracic echocardiograms were performed on 125 AxSpA patients and 56 age-matched controls. Leading edge aortic root (AoR) measurements were made and normalized for body size. Measurements were also taken at the aortic annulus, sino-tubular junction and ascending aorta. DD was graded according to the American Society of Echocardiography guidelines. Chi square tests and Wilcoxan rank sum analyses were used in the univariate analysis. A subgroup analysis was performed in a matched group of 90 AS patients meeting the modified New York criteria and 45 healthy controls. Results: Participants were 68% male with a mean age of 43 ± 12 years. Mean AxSpA disease duration was 18 ± 12 years. mSASSS for the overall AxSpA population was 7.1 ± 14.5 units and was 9.9 ± 16.5 units for the AS population. Mean AoR diameter was 3.29 ± 0.36 cm for cases and 3.24 ± 0.32 cm for controls. There were no differences in linear aortic measurements, AI or DD between groups. The subgroup analysis of AS patients alone did not show differences in any of these outcomes when compared to controls. Conclusions: AxSpA patients showed no differences in AoR size or AI when compared with healthy controls. While there were differences among individual measurements used to assess diastology, there is no clinically relevant difference in DD between groups. These findings are the first evidence-base to support the recommendations against routine echocardiographic screening in asymptomatic AxSpA patients. References: Nagueh SF, et al. Recommendations for the evaluation of left ventricular diastolic function by echocardiography. Journal of the American Society of Echocardiography 22.2(2009):107–133. Disclosure of Interest: None declared